DECLINE OF THE NOTION OF LEGAL CUSTOM THROUGH THE SPECIFICITIES OF ARTIFICIAL INTELLIGENCE - Stancu, Radu (International Journal of Legal and Social Order, 2024)
The present study aims to explore the transformations brought to custom, a traditional source of law, by the emergence of artificial intelligence (AI). The plan of the analysis is structured in two main parts: the first part focuses on the presentation of the notion of custom and its particularities in relation to usage. The second part of the paper develops the concept of AI and its functions, in particular that of the legal algorithm. The central issue around which this article is articulated is the protection of fundamental rights and free will, since AI tends to take the place of the legislator, producing new social rules based only on factual data, which lack the power of abstraction.